Current issues of environmental safety in landscape architecture - Portnova Тatiana V.; Portnova, Irina V. (International Journal of Innovative Research and Scientific Studies, 2025)
The article considers current environmental safety issues in landscape architecture. It analyses the contemporary approaches to ensuring the sustainability of landscape solutions in the context of an urbanised environment. The paper explores innovative methods for designing environmentally safe landscape complexes taking into account natural and climatic factors, and as well as anthropogenic loads. It presents an analysis of the effectiveness of modern technologies in creating sustainable landscape systems. A number of recommendations for the implementation of environmentally safe solutions in landscape design practice have been developed, as based on the findings of the research. Some promising areas for the development of the industry with regard to the principles of environmental safety and sustainable development of territories have been identified.